2022
DOI: 10.24868/10729
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Collision-avoidance Capabilities Reduction After a Cyber-Attack to the Navigation Sensors

Abstract: The interest in autonomous navigation for surface ships has arisen over the years for both naval vessels and commercial ships. In literature, several pieces of research addressed the challenges of developing new guidance laws, stable and robust control algorithms, methodologies to increase situational awareness, and collision avoidance algorithms. Current papers base their outcome on blind trust in the information coming from navigation sensors. However, sensors can be subjected to malfunctioning, or even wors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…It may be possible to insert "a few pixels"-invisible to the human eye-which "can make an AI misidentify a stop sign for a 45 MPH sign" (Woodie, 2020). In the maritime sector, research by Longo et al (2022) has shown that they can insert radar blips and "delete existing ones, which is really nasty as a vulnerability" (Interview with computer engineering researcher, 2022). In a separate experiment, Longo demonstrated, that, knowing COLREG Rule 14-i.e., when two ships are approaching head on both ships must alter course to starboard-gives hackers a kind of "superpower."…”
Section: Cybersecurity In Conventional and Uncrewed Shipsmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be possible to insert "a few pixels"-invisible to the human eye-which "can make an AI misidentify a stop sign for a 45 MPH sign" (Woodie, 2020). In the maritime sector, research by Longo et al (2022) has shown that they can insert radar blips and "delete existing ones, which is really nasty as a vulnerability" (Interview with computer engineering researcher, 2022). In a separate experiment, Longo demonstrated, that, knowing COLREG Rule 14-i.e., when two ships are approaching head on both ships must alter course to starboard-gives hackers a kind of "superpower."…”
Section: Cybersecurity In Conventional and Uncrewed Shipsmentioning
confidence: 99%
“…In a separate experiment, Longo demonstrated, that, knowing COLREG Rule 14-i.e., when two ships are approaching head on both ships must alter course to starboard-gives hackers a kind of "superpower." In "97,000 computer simulations" they were able to show collision avoidance algorithms would predictably maneuver a ship to a location specified by the hackers (Longo et al, 2022). Longo and colleagues warn against "blind trust in the information coming from navigation sensors" and that "sensors can be subjected to malfunctioning, or even worse, cyber-attackers may hijack their data.…”
Section: Cybersecurity In Conventional and Uncrewed Shipsmentioning
confidence: 99%
See 1 more Smart Citation
“…For S(f ||u) ≥ 0, log(b − a) ≥ h(x), i.e., no distribution can can have greater entropy than that of the uniform distribution [11,12].…”
Section: A Extensive and Nonextensive Statisticsmentioning
confidence: 99%